The bond between intelligences: cultural, emotional, and social - Samy, Naresh Kumar; Che Rose, Raduan; Subramaniam, (International Society for Performance Improvement, 2008)
Increasing interest in multiple forms of nonacademic intelligences in addition to the well-established intelligent quotient (IQ) to explain individual success has triggered a need for clear establishment of the theoretical and empirical connection among these constructs. As such, this article explores the interrelationship that exists among three forms of nonacademic intelligences: cultural, emotional, and social. Theoretical and practical implications are also discussed.